W obronie tożsamości człowieka – globalizacja jako przyczyna modernizacji współczesnych systemów oświaty - Markiewicz, Elżbieta (Studia Edukacyjne, 2017)
The article In Defense of Human Identity: the Reality of Globalization as the Cause of Modernization of Modern Educational Systems is an attempt to reflect on the role of the educational process in the context of the value system offered in the modern world. It appears that authentic human participation in the reality of global and involuntary compliance with the directives of globalism is both a crisis of identity, of its existence, values, norms, and all human activities. Efforts taken to demonstrate the value of dogma, which carries with it an affirmation of the modern world, and conformist standards of conduct, is to notice the risk of objective truth about man and reality. Civilization implies in fact a kind of order to eradicate what is human. The human drama shows an almost total devotion to the values of functionalism and utility. Therefore, it is vital for modern education to return to the personal dimension of human existence. This accomplishment, a full range of education, which means clarifying the challenges confronting it, is only possible with recognizing and highlighting the personal status of the man based on the personalistic norm. This article helps the contemporary human being to realize the importance of learning to respect human dignity and to protect the identity of a mature man